The Survey on Students’ Satisfaction Degree towards Online Learning during Covid-19 Pandemic Condition - Taufik; Fiptar Abdi Alam (Universitas Muhammadiyah Barru, 2022)
The present study aimed at describing the satisfaction level of the university students in online learning at STKIP Muhammadiyah Barru during the Covid-19 pandemic situation. The research participants were 30 students of the Guidance and Counseling study program in the first semester on the academic year of 2021/2022. To collect data, researchers distributed questionnaire items to participants via Google forms, then analyzed the data qualitatively. The result of students’ responses to the questionnaire showed that in overall, 14 students (46.7%) of Guidance and Counseling Study Program at STKIP Muhammadiyah Barru were satisfied with the implementation of online learning organized by the campus, 10 other students (33.3%) stated that they were very satisfied, although there were also a small number namely 6 students (20%) expressed dissatisfaction. The satisfaction of the majority of students were found in the lecturers’ role factor as a facilitator, and the good communication interaction factor to lecturers and to classmates. Students’ dissatisfaction was generally found in the learning effectiveness factor, where students stated that they were bored with the independent assignments given by lecturers via online.